(untitled) (Research, Society and Development, 2019)
This qualitative and exploratory study aims to understand the implications of the conjugal separation in the psychic development of children from 0 to 6 years in the psychoanalytic perspective of Freud and Winnicott in order to verify the implications of divorce in the psychic development of children from 0 to 6 years from Psychoanalysis. It has been found as a result that children may experience feelings of abandonment, guilt, parental or aggressive fantasies of reconciliation, undergo oedipal reorganization and can often be placed by parents in a position which can not meet the demand. It was concluded that children should continue to receive attention, affection and being narcissistically invested by both parents, that divorce is a time of crisis, however, the implications of marital separation depend very much on the behavior of parents toward the child and the relationship between them.